Kinematic constraint analysis in a twin-robot system for curved-surface nondestructive testing. Issue 2 (21st March 2016) - Lu, Zongxing; Xu, Chunguang; Pan, Qinxue; Xiao, Dingguo; Meng, Fanwu; Hao, Juan
Abstract : Purpose: – Nondestructive testing based on cooperative twin-robot technology is a significant issue for curved-surface inspection. To achieve this purpose, this paper aims to present a kinematic constraint relation method relative to two cooperative robots. Design/methodology/approach: – The transformation relation of the twin-robot base frame can be determined by driving the two robots for a series of handclasp operations on three points that are noncollinear in space. The transformation relation is used to solve the cooperative motion problem of the twin-robot system. Cooperative motions are divided into coupled and combined synchronous motions on the basis of the testing tasks. The position and orientation constraints for the two motion modes are also explored. Findings: – Representative experiments between two industrial robots are conducted to validate the theoretical developments in kinematic constraint analysis. Artificial defects are clearly visible in the C-scan results, thereby verifying the validity and the effectiveness of the proposed method. Originality/value: – The transformation relation of the twin-robot base frame is built under a series of handclasp operations. The position and orientation constraints for the coupled and combined synchronous motions are explored. Theoretical foundations of trajectory planning method for the transmitting and receiving transducers of the cooperative twin-robot system are presented.